Factors influencing credit card usage in Malaysia / Sharifah Nurhidayah Wan Mohamad Jaya - Wan Mohamad Jaya, Sharifah Nurhidayah (Faculty of Business and Management, 2019)
The present study seeks to examine the factors influencing credit card usage in Malaysia. The independent variables consist of five factors including convenience, credit card usage knowledge, status, bank’s policies and attitude towards money. Meanwhile the dependent variable of this study is credit card usage. A total of 299 usable questionnaires was keyed in and analysed by using SPSS software version 20. Furthermore, this research has used non-probability, convenience sampling to obtain accurate data from targeted respondents. All the data were collected for the purpose to create analysis of descriptive, correlation and regression analysis. In this study, findings show that there were two independent variables that has a significant relationship towards credit card usage which are convenience and credit card usage knowledge. From this we see, the finding is useful for banking industry and government on the pattern of credit card usage in Malaysia so that they can amend better policies and regulations to control bankruptcy.